THE PROGNOSIS OF THE RESULTS OF DOUBLE-COMPONENT ANTIHYPERTENSIONAL THERAPY ACCOUNTING MEANINGS OF MIDDLE DAILY HEART RATE AND NON-MODIFIED RISK FACTORS - Yabluchansky, N.I.; Datsenko, H.G. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In the grounds of complex examination of 300 patients with essential arterial hypertension the mathematical pattern of prognosis the results of double-component antihypertention therapy by enalaprili maleatum (10 mg per day) and hydrochlortiasidum (25 mg per day) was worked out. Accounted the initial meanings of middle daily heart rate (HR) non-modified risk factors (the blood pressure (BP) level, the type of somato-vagal balance and the type of left ventricular geometry). It was started, that good results of  lowering BP in the double-component antihypertentional therapy by enalaprili maleatum (10 mg per day) and hydrochlortiasidum (25 mg per day) correspond the probabily of 70%, setisfed results of normalisation - the probabily of 50-70%, dissetistole results - the probabily of less then 50%. The  double-component antihypertentional therapy by enalaprili maleatum (10 mg per day) and hydrochlortiasidum (25 mg per day) is shown to the patients with the probability of BP normalization more than 70%.